Front Cover: Deracemization in a Complex Quaternary System with a Second‐Order Asymmetric Transformation by Using Phase Diagram Studies (Chem. Eur. J. 61/2019). Issue 61 (20th September 2019) - Oketani, Ryusei; Marin, Francesco; Tinnemans, Paul; Hoquante, Marine; Laurent, Anne; Brandel, Clément; Cardinael, Pascal; Meekes, Hugo; Vlieg, Elias; Geerts, Yves; Coquerel, Gérard
Abstract : Phase diagrams play a critical role for tuning crystallization. This study explains the basics of phase diagrams starting from the ternary system to a quaternary system with and without fast racemization in the liquid phase. Experimentally, an atropisomeric naphthamide derivative in MeOH/H2 O serves as an example. Deracemization is ensured by a second‐order asymmetric transformation up to 97%  ee . Readers are encouraged to look at the animation (in the Supporting Information) detailing the construction of the degenerated quaternary system in a step‐by‐step manner. More information can be found in the Full Paper by G. Coquerel et al. on page 13890 .